2021
DOI: 10.3390/rs13183574
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Based Human Settlement Datasets Inadequately Detect Refugee Settlements: A Critical Assessment at Thirty Refugee Settlements in Uganda

Abstract: Satellite-based broad-scale (i.e., global and continental) human settlement data are essential for diverse applications spanning climate hazard mitigation, sustainable development monitoring, spatial epidemiology and demographic modeling. Many human settlement products report exceptional detection accuracies above 85%, but there is a substantial blind spot in that product validation typically focuses on large urban areas and excludes rural, small-scale settlements that are home to 3.4 billion people around the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Remote sensing research often uses satellite data to examine socioeconomic and environmental issues relevant to critical scholarship. Across the social and environmental sciences, studies by economists, political scientists, geographers, and others have used satellite imagery to expose the presence and/or effects of corruption (Hodler and Raschky, 2014), inequality (Ivan et al, 2020; Zhou et al, 2015), poverty (Briggs, 2018), unequal distribution of public services like electricity (Min et al, 2013; Min and Gaba, 2014), natural disasters (Gillespie et al, 2014), conflict (Agnew et al, 2008; Cederman et al, 2015; Coscieme et al, 2017), refugee movements, settlements, and forced migrations (Ahmed et al, 2019; Van Den Hoek and Friedrich, 2021; Witmer and O’Loughlin, 2011), and mass atrocities and genocide (Marx et al, 2019). Remote sensing has also been used to expose deforestation driven by refugee camps (Ahmed et al, 2019; Hassan et al, 2018), illegal mining (Kyba et al, 2019), gas flaring (Elvidge et al, 2013), and illegal fishing (Hsu et al, 2019; Lumban-Gaol et al, 2020).…”
Section: Practices Of Critical Remote Sensing: Expose Engage Empowermentioning
confidence: 99%
“…Remote sensing research often uses satellite data to examine socioeconomic and environmental issues relevant to critical scholarship. Across the social and environmental sciences, studies by economists, political scientists, geographers, and others have used satellite imagery to expose the presence and/or effects of corruption (Hodler and Raschky, 2014), inequality (Ivan et al, 2020; Zhou et al, 2015), poverty (Briggs, 2018), unequal distribution of public services like electricity (Min et al, 2013; Min and Gaba, 2014), natural disasters (Gillespie et al, 2014), conflict (Agnew et al, 2008; Cederman et al, 2015; Coscieme et al, 2017), refugee movements, settlements, and forced migrations (Ahmed et al, 2019; Van Den Hoek and Friedrich, 2021; Witmer and O’Loughlin, 2011), and mass atrocities and genocide (Marx et al, 2019). Remote sensing has also been used to expose deforestation driven by refugee camps (Ahmed et al, 2019; Hassan et al, 2018), illegal mining (Kyba et al, 2019), gas flaring (Elvidge et al, 2013), and illegal fishing (Hsu et al, 2019; Lumban-Gaol et al, 2020).…”
Section: Practices Of Critical Remote Sensing: Expose Engage Empowermentioning
confidence: 99%
“…However, there is still significant disagreement between these global datasets in rural areas [13,14], where most refugee camps are located. Previous studies have shown that GP maps underrepresent populations in refugee camps in Uganda [15] and informal settlements in Kenya [16]. However, the utility of global data in the context of refugee flood risk has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The need for tailored, systematic vulnerability assessments is arguably the most acute for refugee camp settings, which are broadly characterized by data scarcity or outright absence 13 , 14 . In planning refugee camps or evaluating potential hazards, refugee camp managers and humanitarian organizations make prioritization and logistic decisions on local to regional scales, often with a lack of high quality, high spatial resolution data.…”
Section: Introductionmentioning
confidence: 99%